EVALUASI KEAMANAN DAM JATILUHUR BERBASIS INDEKS RESIKO - Avazbek Ishbaev; Nora H. Pandjaitan; - Erizal (Graduate School Bogor Agricultural University (SPs IPB), 2014)
The dams have very important roles to agricultural activities. Especially, West Java with 240,000 hectares of agricultural land, needs a good dam structure that can be used sustainably. Jatiluhur dam in Purwakarta, West Java is one of big dams in Indonesia which has important rules not only for Purwakarta but also for Jakarta, Karawang and Bekasi residents. A study and observation about safety and dam stability is needed to prevent any damage. The purpose of this research were to identify parameters that influenced dam safety and to evaluate dam reliability based on index tools. Analysis was done using risk index tools. The result showed that the condition of the dam of Jatiluhur is still satisfied with indicators,